Proyecto de expansión para el cyber café Sh-Net Sistemas - Jácome Molina, Edgar Daniel (2010)
Facing the detailed situation in the problem to study we can determine that SH-NET SYSTEMS, his background and experience in the rental activity short- and long-term computer equipment, you need to expand your business, thus allowing a further increase in the market; situation which is necessary and required an expansion project for the business. The project is focused on the management and analysis of expansion strategies, which will achieve the economic returns, financial and quality that customers expect owners and medium term.